Applying Listen English Daily Practice Application to Improve Students Listening Skills - Azizah, Nur; Nadrun, Nadrun; Hasyim, Zarkiani; Kusuma Dewi, Anjar (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research aims to investigate the effectiveness of the Listen English Daily Practice application to improve the listening skills of tenth-grade students at SMK Negeri 8 Palu. The study used a quasi-experimental design by Cohen et al. (2005:214) with pre-test and post-test given to both the experimental and control classes. Class X Mining Geology A was assigned as the experimental group and class X Mining Geology B as the control class, each consists of 25 students. Data were analyzed using SPSS. The results showed that students in the experimental class achieved a significantly higher post-test score compared to the control group, with a mean increase from 56.64 to 79.12. This indicates that the use of the Listen English Daily Practice application is considered an effective medium to improve students’ listening skills. The application’s features, such as vocabulary lists, audio transcripts, and interactive tests, contributed to increased motivation and independent learning.